Corrigendum: Language, Meaning, and Games: A Model of Communication, Coordination, and Evolution - Demichelis, Stefano; Weibull, Jörgen W. (American Economic Review, 2009)
Corrigendum: Language, Meaning, and Games: A Model of Communication, Coordination, and Evolution by Stefano Demichelis and Jörgen W. Weibull. Published in volume 99, issue 5, pages 2277 of American Economic Review, December 2009